La–Mo binary metal oxides for oxygen evolution reaction. (3rd February 2021) - Rani, B. Jansi; Keerthana, S.P.; Yuvakkumar, R.; Ravi, G.; Velauthapillai, Dhayalan; Shivatharsiny, Yohi; Babu, E. Sunil; Almoallim, Hesham S.; Alharbi, Sulaiman Ali
Abstract: In this study, the role of pH in a material's phase, morphology, and electrochemical properties was thoroughly investigated by producing lanthanum molybdates. The investigated samples were designed as electrodes for the electrochemical water oxidation process to produce clean energy in a half-cell fabrication. An excellent electrochemical water oxidation was demonstrated by La2 Mo2 O7 at pH7, which showed an outstanding 241 ± 1 mA/g current density with very low (197 mV) overpotential. This is a quite good output obtained from such binary metal oxides. Furthermore, lower Tafel slope (59 mV/dec) was observed for the same candidate along with early oxygen evolution reaction (OER) because of ion migrations. Interestingly, 99% activity retention was evidenced for the optimized candidate over 16 h in a half-cell design. The findings of this study may generate great interest among young researchers in developing novel bimetal oxides for robust and sustainable water electrolysis to produce clean energy. Highlights: An excellent electrochemical water oxidation was demonstrated. La2 Mo2 O7 exhibited outstanding 241 ± 1 mA/g current density. La2 Mo2 O7 exhibited very low 197 mV overpotential. 99% of activity retention was evidenced over 16 h.